(untitled) (Biological Sciences - PJSIR, 2002)
The inorganic phosphate (Pi) contents of the muscles of some economically important Red Sea teleosts were determined. The fish species included were of different feeding habits: carnivorous, omnivorous and herbivorous. Herbivore group showed the highest level of inorganic phosphate followed by omnivore and carnivore. The variations of the total content of inorganic phosphate existed in the muscle of fish of the same feeding habit do exist.